(untitled) (Bangladesh Journal of Urology, 2020)
A 20 year old female was diagnosed, clinically, radiologically and by FNAC as a case of benign renal mass. She was observed for 5 months and on reevaluation by contract enhanced CT scan of abdomen revealed, contrast enhancing well demarcated mass with stable size. She was then planned for enucleation and frozen section biopsy. Per operatively, mass were easily enucleated but frozen section shows malignancy hence nephrectomy was done. Histopathological report showed; renal cell carcinoma, clear cell type and TNM staging; T1b Nx M0. Hence in this paper, we have reviewed the article regarding RCC in young age and a diagnostic dilemma of RCC in young age. Bangladesh Journal of Urology, Vol. 21, No. 1, January 2018 p.43-47